Control of Scutellonema bradys in yam tubers by Streptomyces spp. - Sousa, Carla (2009)
This study aimed to evaluate the effect of estreptomycets on the control of the nematode Scutellonema bradys in yam tubers. A bioassay was set in the laboratory using Elisa plates in a completely randomized design. Amounts of 200 μL of metabolites of each of the five isolates of estreptomycets were used with 100 nematodes. Drinking water served as control, in a total eight replicates (each replicate consists of a cavity plate). The percentage of dead nematodes was determined after a period of 24 hours. The mortality rates of S. Bradys in the metabolites ranged from 87.2% to 100%. In a greenhouse an experiment was installed in a randomized block design where tubers were immersed for 24 hours in suspension containing seed of each of the three isolated from estreptomycets assessed or in drinking water (control treatment), with 10 repetitions (each replicate consists of a pot with two plants).The tubers-seed were planted in sterile soil and fifteen days after germination was carried out the inoculation of 2000 nematodes per plant. The assessment of nematodes per tuber was conducted five months after inoculation. There was a reduction of 84.5% to 95.4% in the number of nematodes in tubers inoculated with the isolated estreptomycets. These results suggest that the isolates from estreptomycets have a potential biocontrol activity against S. bradys.